ATPase activity of transcription-termination factor rho: functional dimer model. - Seifried, S E (1992)
Transcription-termination factor rho of Escherichia coli functions as an RNA-dependent ATPase that causes transcript release at specific rho-dependent termination sites on the DNA template. Rho exists as a hexagon of identical subunits, physically organized as a trimer of dimers with D3 symmetry. The structural asymmetry of the dimer is reflected in the binding properties of rho; each dimer has a strong and a weak binding site for both the ATP substrate and the RNA cofactor. Here we use homopolynucleotides in competition and complementation experiments to characterize the ATPase activation properties of the cofactor binding sites of the functional rho dimer. We show that (i) no ATPase activity is observed unless both the high- and the low-affinity cofactor binding sites of the functional rho dimer are occupied; (ii) saturating levels of poly(rC), poly(rC) in combination with poly(rU), or poly(rU) alone can fully activate the ATPase of rho; and (iii) poly(dC) can serve as a fully competitive inhibitor of half of the ATPase activity of rho when one of the cofactor sites is filled with poly(rC). These observations lead to a set of phenomenological rules that describe the cofactor dependence of the ATPase activation of the functional dimer of rho and help to define a mechanistic basis for interpreting rho function in termination.